Alterações de propriedades físico-hídricas em solos arenosos do bioma Pampa sob usos distintos - Galarza, Rodrigo de Moraes (2023)
The naturally fragile sandy soils of the pampa biome (BP) are being degraded with the introduction of poorly managed agricultural crops. Anthropic use can markedly decrease vegetation cover on sandy soils, leaving them more exposed to erosive agents. Decreases in organic matter content, biodiversity, and nutrient availability, increased soil compaction, and lower water availability are also some crops. In Rio Grande do Sul, in areas with sandier soils, the intense BP replacement for commercial crops that occurred in recent years (2000-2020) may be initiating a disastrous cycle of degradation of these soils. However, it is not yet known how much these soils are degraded by recent anthropic use. There are no local scientific publications dedicated to the diagnosis of the degradation of these soils by anthropic use. Therefore, the need for this study was based on the objective of evaluating the physical and hydraulic properties of BP sandy soils with the insertion of agricultural crop soils. The study was conducted on three different soils, where soil samples were collected under three use systems (extensive cattle ranching on native pastures, eucalyptus afforestation, and soybean crops). Our results show that these sandy soils can take more than 10 years to indicate some levels of degradation in their physical and hydraulic properties after replacement of BP by annual crops.